Medical studies in Yurimaguas - Weiss, Pedro (1942)
A medical study made at Yurimaguas, a village located on the Lower Huallaga, in the Peruvian Forest Country. The author found intestinal parasitism to be the disease most frequently met with, with ankylostomiasis predominating. He al so came across cases of Yaws, juxta-articular tumours, "Lajs", Leihsmaniasis ( Espundia), Phagedenic tropical uIcers, Pinta, Tropical Vitiligo, Infantile Paralysis, Malaria fever (with P. Malarie predorninating) and Pterygion. No cases of American Trypanosomiasis, Filariasis, Beri-beri, Yellow fever, or even Leprosy were discovered. Compared with other places in the Peruvian Forest Country, Yurimaguas is a healthy place. Apart from intestinal parasitism, the percentage of other diseases, is relatively low.